Lobaplatin-based neoadjuvant chemotherapy for triple-negative breast cancer: a 5-year follow-up of a randomized, open-label, phase II trial. (June 2022) - Yan, Wenting; Wu, Xiujuan; Wang, Shushu; He, Cheng; Zhong, Ling; Tang, Peng; Ren, Lin; Zhang, Ting; Qi, Xiaowei; Zhang, Yi
Purpose: We report the 5-year follow-up findings of a randomized, open-label, phase II trial of lobaplatin-based neoadjuvant chemotherapy plus adjuvant therapy for triple-negative breast cancer (TNBC). Patients and methods: This study included patients aged ⩾18 years with untreated, operable stage I–III TNBC and an Eastern Cooperative Oncology Group performance status of 0 or 1. One group of patients (TE group, n  = 99) received four cycles of docetaxel (T, 75 mg/m²) plus epirubicin (E, 80 mg/m²) every 3 weeks, and another group (TEL group, n  = 101) received the same treatment with the addition of lobaplatin (L, 30 mg/m 2 ). Two cycles of the corresponding treatments were administered after surgery in both groups. The primary endpoints were total pathological complete response (tpCR) rate and overall response rate (ORR), and the secondary endpoints were disease-free survival, overall survival, and long-term safety. This trial is registered with the Chinese Clinical Trial Registry (ChiCTR-TRC-14005019). Results: The median follow-up was 48.2 months (interquartile range: 31.1–60.0). The tpCR rate was 41.4% and 17.8% in the TEL group and TE group, respectively ( p  < 0.001). The HR for comparison of DFS between the TEL group and TE group was 0.44 (95% CI: 0.21–0.90, P p  = 0﻿.028). The addition of lobaplatin resulted in an HR of 0.44 (95% CI: 0.18–1.02, P  = 0.061) for the difference in OS between the two groups. The ORR, which included complete response and partial response, was 92.9% in the TEL group and 74.3% in the TE group ( p  = 0.001). The TEL group patients were more likely to develop grade III–IV anemia and thrombocytopenia. No lobaplatin-related deaths or increased risk of long-term toxicity was observed. Conclusion: Neoadjuvant lobaplatin therapy can improve the tpCR and ORR rates of TNBC with tolerable side effects and have a tendency to improve the long-term survival.